Genotypic and Phenotypic Characterization of Clinical Escherichia coli Sequence Type 405 Carrying IncN2 Plasmid Harboring blaNDM-1 - Hao, Yingying; Shao, Chunhong; Geng, Xu; Bai, Yuanyuan; Jin, Yan; Lu, Zhiming (Frontiers in Microbiology, 2019)
We report a carbapenem-resistant Escherichia coli with blaNDM-1 isolated from the abdominal fluid of a patient at a teaching hospital and and was found harboring blaNDM-1. This blaNDM-1-producing E. coli belonged to phylogenetic group D, sequence type (ST) 405. We thus aimed to illustrate the genotype and phenotype of blaNDM-1-producing ST405 E. coli in China. In addition to blaNDM-1, this isolate carried the acc(6’)-Ib gene and the extended-spectrum β-lactamase genes blaCTX-M-15 and blaCTX-M-14. blaNDM-1 is located on a self-transmissible plasmid designated as pJN24NDM1-1 and referred as IncN2. pJN24NDM1 was completely sequenced and compared with eight published IncN2 plasmids harboring carbapenem-resistance genes. pJN24NDM1-1 is almost identical to pYNKP001-NDM, pNDM-ECS01, and pTR3 from different bacteria, suggesting a common distribution and transmission in Asia. Our research indicates that E. coli carrying IncN2 plasmids act as a reservoir and play an important role in the spread of blaNDM. Further molecular epidemiological studies are needed to monitor the multidrug resistant virulent clones to prevent further dissemination.